2015
DOI: 10.1002/pmic.201500162
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of ionomycin‐induced ascidian sperm reaction: Released and exposed sperm proteins in the ascidian Ciona intestinalis

Abstract: Sperm proteins mediating sperm-egg interaction should be exhibited on the sperm surface, or exposed or released when sperm approach an egg. In ascidians (protochordates), sperm undergo a sperm reaction, characterized by enhanced sperm motility and mitochondrial swelling and shedding on contact with the vitelline coat (VC) or by treatment with Ca(2+) ionophore. Here, proteomic analysis was conducted on sperm exudates and sperm surface proteins using ionomycin-induced sperm reaction and cell-impermeable labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 65 publications
1
15
2
Order By: Relevance
“…We previously reported (Nakazawa, Shirae‐Kurabayashi, Otsuka, & Sawada, ) that a PNA‐Alexa Fluor conjugate labels an intracellular region alongside the nucleus rather than the acrosome in sperm of the ascidian Ciona robusta (Hoshino & Tokioka, ) (formerly referred to as C. intestinalis type A; see [Brunetti et al, ; Pennati et al, ] for details), in contrast to our expectation that it would detect the acrosome. The existence of a novel PNA‐binding region in C. robusta suggests that glycans similar to those present in the mammalian acrosome are also accumulated in this sperm region.…”
Section: Introductioncontrasting
confidence: 74%
See 3 more Smart Citations
“…We previously reported (Nakazawa, Shirae‐Kurabayashi, Otsuka, & Sawada, ) that a PNA‐Alexa Fluor conjugate labels an intracellular region alongside the nucleus rather than the acrosome in sperm of the ascidian Ciona robusta (Hoshino & Tokioka, ) (formerly referred to as C. intestinalis type A; see [Brunetti et al, ; Pennati et al, ] for details), in contrast to our expectation that it would detect the acrosome. The existence of a novel PNA‐binding region in C. robusta suggests that glycans similar to those present in the mammalian acrosome are also accumulated in this sperm region.…”
Section: Introductioncontrasting
confidence: 74%
“…Exposure of the PNA‐binding region of C. robusta sperm following ionomycin treatment (Nakazawa et al, ) was not observed under our experimental conditions. This was puzzling given that the phenomenon was observed at least twice in our previous experiments (e.g., Figure d).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…CBB-stained protein bands were excised from the polyacrylamide gel and subjected to in-gel digestion, LC/MS, and a database search, as described previously (Nakazawa et al, 2015). Briefly, samples were reduced with dithiothreitol and carbamidometh-ylated and carbamidomethylated, digested with modified trypsin (V511A; Promega, Madison, WI, USA), separated in an octadecyl silica gel column over a gradient of acetonitrile containing 0.1% formic acid, and analyzed with a mass spectrometer (LTQ-XL; Thermo Fisher Scientific) equipped with an electrospray ionization unit.…”
Section: Liquid Chromatography/mass Spectrometry (Lc/ms)mentioning
confidence: 99%